Circulating levels of the chemokine CCL18 but not CXCL16 are elevated and correlate with disease activity in rheumatoid arthritis. Issue 10 (9th March 2007) - van Lieshout, Antoine W T; Fransen, Jaap; Flendrie, Marcel; Eijsbouts, Agnes M M; van den Hoogen, Frank H J; van Riel, Piet L C M; Radstake, Timothy R D J
Abstract : Background: Antigen-presenting cells (APC) and T cells are considered to play a significant role in the pathogenesis of rheumatoid arthritis (RA). CCL18 and CXCL16 are two chemokines that facilitate T cell attraction by APC, of which a role in the pathogenesis of RA has been suggested. Objective: To compare the circulating levels of CXCL16 and CCL18 in RA with controls and to investigate the relation of CXCL16 and CCL18 with RA disease activity and joint damage. Methods: Circulating CCL18 and CXCL16 levels were determined in 61 RA patients with a follow-up of 6 years and a group of 41 healthy controls with ELISA. Chemokine levels were correlated with demographic data, disease activity (DAS28) and joint damage (modified Sharp score). In addition, serum CCL18 and CXCL16 levels from a cohort of 44 RA patients treated with anti-TNF-α were correlated with disease activity. Results: CCL18 levels in serum were significantly elevated in RA patients compared with controls, while serum CXCL16 levels were not. In contrast to CXCL16, serum CCL18 was positively correlated with disease activity. Both CCL18 and CXCL16 levels decreased upon treatment with anti-TNF-α. Neither CCL18 nor CXCL16 correlated with joint damage and progression. Conclusion: Here, we show, for the first time, that circulating CCL18 and not CXCL16 levels are elevated in RA patients as compared with controls and correlate with disease activity in RA. More knowledge regarding the regulation and function of both CCL18 and CXCL16 is essential to value their role in RA.